Lymphoedema management by independent hospices: a cohort study. Issue 4 (3rd October 2019) - Brown, Andrea; Nicholson, Carol; Fearing, Adam; Newton, Julia; Gordon, Simon; Hughes, Andrew; Egdell, Andrea; Ellam, James
Abstract : Objectives: To consider the type and cost of clinical services delivered for patients with lymphoedema. Design: Clinical cohort. Setting: Independent hospices in the North East of England. Participants: All those attending lymphoedema services delivered by the independent hospice sector 2017/2018. Results: 13 914 lymphoedema appointments were recorded across four independent hospices. Twelve thousand nine hundred and sixty-five were attended, which equates to an approximate cost of £1.56 million. Those with lymphoedema were predominately aged over 65 (54.5%) years with females across all age groups being more predominant (3.3:1). Where the cause was recorded, 66% of activity related to lymphoedema was not secondary to cancer. Conclusion: Independent hospices are providing a specialist lymphoedema service, which is high in volume and largely invisible. This service is delivered at not insignificant cost. In contrast to previous work, in the North East of England, lymphoedema sufferers are more likely to be female and not have the condition in association with cancer. The availability of rigorous data collection will allow the independent hospices to understand better the delivery and associated costs of lymphoedema services.